2021
DOI: 10.1186/s12876-021-01706-8
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics of acute pancreatitis in children: a single-center experience in Western China

Abstract: Background The diagnosis of pediatric pancreatitis has been increasing over the last 20 years. We aimed to compare the clinical characteristics for pediatric acute pancreatitis (AP) with adult AP, and investigate the risk factor for acute recurrent pancreatitis (ARP) in children. Method From June 2013 to June 2019, a total of 130 pediatric patients with AP at the inpatient database were enrolled. Univariate analysis and multivariate Cox regression … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 32 publications
2
9
2
Order By: Relevance
“…This study shows that the incidence of SAP in pediatric AP was 10.2%, which is similar to a previous report (12.8%) [4]. The severity of AP in children is lower than that in adults, which may be related to the etiology, complications, and pancreatic necrosis [14]. In this study, the incidence of acute necrotic collection was 2.9%, which was lower than that in a previous study (4.6%) [14].…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…This study shows that the incidence of SAP in pediatric AP was 10.2%, which is similar to a previous report (12.8%) [4]. The severity of AP in children is lower than that in adults, which may be related to the etiology, complications, and pancreatic necrosis [14]. In this study, the incidence of acute necrotic collection was 2.9%, which was lower than that in a previous study (4.6%) [14].…”
Section: Discussionsupporting
confidence: 86%
“…The severity of AP in children is lower than that in adults, which may be related to the etiology, complications, and pancreatic necrosis [14]. In this study, the incidence of acute necrotic collection was 2.9%, which was lower than that in a previous study (4.6%) [14]. Raizner et al reported necrotizing pancreatitis developed in less than 1% of pediatric AP and they suggested that necrotizing pancreatitis in children was associated with severe acute and late complications in children [15].…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Poddar et al studied 320 children with AP in India in 2017 and found that trauma (21%) and biliary tract diseases (10%) were the most common causes of AP in children [ 15 ]. Zhong et al (2021), from China, studied 130 children with AP and found that biliary tract diseases (31%) and idiopathic (28%) were the most common risk factors [ 16 ]. In another study of 115 children in the United States published in 2019, idiopathic (31%) and drugs (23%) were the most common risk factors.…”
Section: Discussionmentioning
confidence: 99%
“…The diseases (31%) and idiopathic (28%) were the most common risk factors [16]. In another study of 115 children in the United States published in 2019, idiopathic (31%) and drugs (23%) were the most common risk factors.…”
Section: Risk Factorsmentioning
confidence: 99%